Colombian vs. American corn: quality, chemical composition, mycotoxin content and metabolizable energy - Aguillón-Páez, Yandy J.; Betancourt, Liliana; Díaz, Gonzalo J. (Revista Colombiana de Ciencias Pecuarias, 2021)
Background: Corn is, quantitatively, one of the most important world crops (ranking second only after wheat) and a key ingredient in animal feeds. Objective: to assess and compare corn quality, mycotoxin content, chemical composition and apparent metabolizable energy (AME) of domestic and imported corn. Methods: Grain quality (USDA grading system) was determined in 30 samples of domestic and 21 samples of imported corn. From each origin, 15 samples were subjected to proximal analysis and 10 were used to determine fatty acid composition. Mycotoxin analysis was conducted on 30 samples of domestic and 23 of imported corn. Results: six of the 30 domestic samples corresponded to US1 grade (highest quality) vs. none of the imported. In the “sample grade” category (lowest quality), 10 and 6 samples corresponded to imported and domestic corn, respectively. Soybeans were found as contaminant in 15 of the 21 imported corn samples. Aspergillus spp. mycotoxins such as ochratoxin A were not detected, and aflatoxins were found in only a few samples at very low levels. Fusariotoxins such as deoxynivalenol and zearalenone were found in 61 and 43% of imported samples, respectively, but in none of the domestic samples. Domestic corn had lower carbohydrate content compared with imported corn (85.4 vs. 86.7%), but higher crude fat (3.8 vs. 3.1%). The AME values for domestic and imported corn were 3,697 and 3,378 kcal/kg, respectively. The fatty acid profiles from both corn types were similar. Conclusion: This study found significant differences between locally-grown and imported corn, particularly in terms of crude fat, AME content, fusariotoxins, and contaminant seeds (soybeans). These findings suggest that locally-grown corn might have nutritional and toxicological advantages over corn imported from the United States.